EKSISTENSI PERKAWINAN ADAT PADA MASYARAKAT MANDAILING DI KOTA MEDAN - AL MAYSITA DALIMUNTHE (PREMISE LAW JURNAL, 2016)
A marriage in Mandailing is called perkawinan manjujur in which the bridegroom’s side gives valuable material or money to the bride’s side. After Law No. 1/1974 on Marriage is in effect, Article 2 of the law states that “A marriage is legitimate when it is done legally according to their respective religions and beliefs.” This research used judicial empirical method. The research result showed that according to Mandailing tradition, a marriage has to follow the Islamic law. The existence of Mandailing community as a tribe or an ethnic group realizes their own identity and cultural unity which makes them feel that they are different from the other communities. Keywords: Existence of Adat Marriage, Mandailing Community